Cervical Ripening Efficacy of Synthetic Osmotic Cervical Dilator Compared With Oral Misoprostol at Term: A Randomized Controlled Trial - Gavara, Rachana; Saad, Antonio F; Wapner, Ronald J; Saade, George; Fu, Anne; Barrow, Ruth; Nalgonda, Swapna; Bousleiman, Sabine; Almonte, Cassandra; Alnafisee, Sarah; Holman, Anita; Burgansky, Anna; et al. (Obstetrics and gynecology, 2022)
OBJECTIVE: To evaluate whether a synthetic osmotic cervical dilator is noninferior to oral misoprostol for cervical ripening. METHODS: In an open-label, noninferiority randomized trial, pregnant women undergoing induction of labor at 37 weeks of gestation or more with Bishop scores less than 6 were randomized to either mechanical cervical dilation or oral misoprostol. Participants in the mechanical dilation group underwent insertion of synthetic osmotic cervical dilator rods, and those in the misoprostol group received up to six doses of 25 micrograms orally every 2 hours. After 12 hours of ripening, oxytocin was initiated, with artificial rupture of membranes. Management of labor was at the physician's discretion. The primary outcome was the proportion of women achieving vaginal delivery within 36 hours of initiation of study intervention. Secondary outcomes included increase in Bishop score, mode of delivery, induction-to-delivery interval, total length of hospital stay, and patient satisfaction. On the basis of a noninferiority margin of 10%, an expected primary outcome frequency of 65% for misoprostol and 71% for mechanical methods, and 85% power, a sample size of 306 participants was needed. RESULTS: From November 2018 through January 2021, 307 women were randomized, with 151 evaluable participants in the synthetic osmotic cervical dilator group and 152 in the misoprostol group (there were four early withdrawals). The proportion of women achieving vaginal delivery within 36 hours was higher with mechanical cervical dilation compared with misoprostol (61.6% vs 59.2%), with an absolute difference of 2.4% (95% CI -9% to 13%), indicating noninferiority for the prespecified margin. No differences were noted in the mode of delivery. Tachysystole was more frequent in the misoprostol group (70 [46.4%] vs 35 [23.3%]; P=.01). Participants in the synthetic osmotic cervical dilator group reported better sleep, less unpleasant abdominal sensations, and lower pain scores (P<.05). CONCLUSION: Synthetic osmotic cervical dilator is noninferior to oral misoprostol for cervical ripening. Advantages of synthetic osmotic cervical dilator include a better safety profile and patient satisfaction, less tachysystole, lower pain scores, and U.S. Food and Drug Administration approval. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT03670836. FUNDING SOURCE: Medicem Technology s.r.o., Czech Republic.
Keywords: dystokie; misoprostol; Administration, Intravaginal; indukovaný porod; Cervical Ripening; zrání děložního hrdla; lidé; aplikace intravaginální; těhotenství; Pregnancy; Dilatation; Oxytocics; ženské pohlaví; Pain; bolest; uterotonika; Dystocia; Labor, Induced; Humans; Misoprostol; dilatace; Female